2014
DOI: 10.1016/j.bbagrm.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

RNAs — Physical and functional modulators of chromatin reader proteins

Abstract: The regulatory role of histone modifications with respect to the structure and function of chromatin is well known. Proteins and protein complexes establishing, erasing and binding these marks have been extensively studied. RNAs have only recently entered the picture of epigenetic regulation with the discovery of a vast number of long non-coding RNAs. Fast growing evidence suggests that such RNAs influence all aspects of histone modification biology. Here, we focus exclusively on the emerging functional interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…The CD is a highly conserved protein module most recognized for targeting methylated histone tails ( Blus et al, 2011 ; Fischle et al, 2003 ). Although several lines of evidence suggest that the CD binds DNA and RNA in addition to targeting methylated histones, its biological relevance and physiological roles are poorly understood ( Hiragami-Hamada and Fischle, 2014 ). In this study, we demonstrated that Suv39h1-CD not only recognizes H3K9me3, but also binds RNA and DNA (with a higher affinity to ssRNA than to dsDNA), indicating that RNA may also be crucial for Suv39h1 recruitment/function.…”
Section: Discussionmentioning
confidence: 99%
“…The CD is a highly conserved protein module most recognized for targeting methylated histone tails ( Blus et al, 2011 ; Fischle et al, 2003 ). Although several lines of evidence suggest that the CD binds DNA and RNA in addition to targeting methylated histones, its biological relevance and physiological roles are poorly understood ( Hiragami-Hamada and Fischle, 2014 ). In this study, we demonstrated that Suv39h1-CD not only recognizes H3K9me3, but also binds RNA and DNA (with a higher affinity to ssRNA than to dsDNA), indicating that RNA may also be crucial for Suv39h1 recruitment/function.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions play important roles in the demarcation of chromatin domains, establishment of specific regional chromatin structures, and regulation of gene expression (Bonasio et al 2010;Smolle et al 2013;Hiragami-Hamada and Fischle 2014) and further highlight the importance of associated factor-mediated processes in the targeting of histone modifiers.…”
Section: Conflicting Reports On Specificity Of Histone Modifiersmentioning
confidence: 99%
“…Early discoveries supported a notion that lncRNA regulate transcription via chromatin modulations 33 . Additionally, several lncRNAs have been found to target directly or indirectly on specific transcription factors 34 .…”
Section: Functional Diversity Of Immune-related Lncrnasmentioning
confidence: 94%